Funeral of Kropotkin. At the monastery of Novodevičy, where Kropotkin is to be burried. Emma Goldman speaks. Under her: Alexander Berkman. Second from the left: Maksimov
Funeral of Kropotkin. At the monastery of Novodevičy, where Kropotkin is to be burried. Emma Goldman speaks. Under her: Alexander Berkman. Second from the left: Maksimov.